Experimental comparison between intensive interventions based on Acceptance and Commitment Therapy and Cognitive Behavioral Therapy for overweight and obese people - Finger da Rosa, Igor; Heinen, Marina; Irigoyen de Freitas, Breno; Ariane Guedes, Patricia; dos Santos Alano, Diego; da Silva Oliveira, Margareth (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
The objective of this study is to investigate the effects of an intervention based on Acceptance and Commitment Therapy (ACT), compared to an intervention based on Psychoeducation and Cognitive Behavioral Therapy (CBT) on objective (weight and body mass index [BMI]) and self-reported measures (binge eating and psychological flexibility) in overweight or obese people. It’s a mixed 2x3 factorial design: Intervention (ACT x Psychoeducation/CBT) and Time (before, after, and five-month follow-up). Seventy-two people were randomly assigned to the groups. The ACT group presented differences in the development of cognitive defusion and food awareness – emotional response, as well as changing binge eating intensity. The other results, including a weight reduction close to 3%, did not show any significant differences between groups. The results indicate that ACT can be an auxiliary modality for the modification of the eating behavior function.